Rivers, people and planning in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Wasting the rain: rivers, people and planning in Africa by W.M. Adams 1992 256pp ISBN 1-85383-089-5 Pbk UKL 12.95 Earthscan Publications Ltd 120 Pentonville Road London N1 9JN, UK